The enrichment paradox in adaptive radiations: Emergence of predators hinders diversification in resource rich environments. (15th January 2022) - Chaparro‐Pedraza, P. Catalina; Roth, Gregory; Seehausen, Ole
Abstract: Adaptive radiations are known for rapid niche diversification in response to ecological opportunity. While most resources usually exist prior to adaptive radiation, novel niches associated with novel resources can be created as a clade diversifies. For example, in African lake cichlid radiations some species prey upon other species of the clade (intraclade consumers). Using a trait‐based eco‐evolutionary model, we investigate the evolution of intraclade consumers in adaptive radiations and the effect of this novel trophic interaction on the diversification process of the radiating clade. We find that the evolutionary emergence of intraclade consumers halts the diversification processes of other ecomorphs as a result of increased top‐down control of density. Because high productivity enables earlier evolution of intraclade consumers, highly productive environments come to harbour less species‐rich radiations than comparable radiations in less productive environments. Our results reveal how macroevolutionary and community patterns can emerge from ecological and microevolutionary processes. Abstract : The evolutionary emerge of consumers within a radiation enhance diversity only when ecological opportunity at the onset is modest. Paradoxically, in environments with extensive ecological opportunity, the evolution of such consumers hinders rather than begets diversity in adaptive radiations, and this effect is most apparent in highly productive environments.